Role of SKD1 Regulators LIP5 and IST1-LIKE1 in Endosomal Sorting and Plant Development - Buono, Rafael Andrade (Plant Physiol, 2016)
SKD1 is a core component of the mechanism that degrades plasma membrane proteins via the Endosomal Sorting Complex Required for Transport (ESCRT) pathway. Its ATPase activity and endosomal recruitment are regulated by the ESCRT components LIP5 and IST1. How LIP5 and IST1 affect ESCRT-mediated endosomal trafficking and development in plants is not known. Here we use Arabidopsis mutants to demonstrate that LIP5 controls the constitutive degradation of plasma membrane proteins and the formation of endosomal intraluminal vesicles. Although lip5 mutants were able to polarize the auxin efflux facilitators PIN2 and PIN3, both proteins were mis-sorted to the tonoplast in lip5 root cells. In addition, lip5 root cells over-accumulated PIN2 at the plasma membrane. Consistently with the trafficking defects of PIN proteins, the lip5 roots showed abnormal gravitropism with an enhanced response within the first 4 h after gravistimulation. LIP5 physically interacts with IST1-LIKE1 (ISTL1), a protein predicted to be the Arabidopsis homolog of yeast IST1. However, we found that Arabidopsis contains 12 genes coding for predicted IST1-domain containing proteins (ISTL1–12). Within the ISTL1–6 group, ISTL1 showed the strongest interaction with LIP5, SKD1, and the ESCRT-III-related proteins CHMP1A in yeast two hybrid assays. Through the analysis of single and double mutants, we found that the synthetic interaction of LIP5 with ISTL1, but not with ISTL2, 3, or 6, is essential for normal plant growth, repression of spontaneous cell death, and post-embryonic lethality.